2017
DOI: 10.1080/1028415x.2017.1337290
|View full text |Cite
|
Sign up to set email alerts
|

Agaricus blazeiextract abrogates rotenone-induced dopamine depletion and motor deficits by its anti-oxidative and anti-inflammatory properties in Parkinsonic mice

Abstract: Neuroinflammation and oxidative damage are the two main malfactors that play an important role in the pathogenesis of experimental and clinical Parkinson's disease (PD). The current study was aimed to study the possible anti-oxidant and anti-inflammatory effects of the methanolic extract of Agaricus blazei (A. blazei) against rotenone-induced PD in mice. Male Albino mice were randomized and divided into the following groups: control, treated with rotenone (1 mg/kg/day), co-treated with rotenone and A. blazei (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Previous studies reported that aqueous extracts of A. blazei offered the neuroprotective effect against the experimental model of Parkinson's disease and aging due to its anti-oxidant, anti-inflammatory, and anti-apoptotic functions (Nakanishi et al, 2014;Venkatesh Gobi et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that aqueous extracts of A. blazei offered the neuroprotective effect against the experimental model of Parkinson's disease and aging due to its anti-oxidant, anti-inflammatory, and anti-apoptotic functions (Nakanishi et al, 2014;Venkatesh Gobi et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 In the present study, injection of rotenone (1 mg/kg) for 21 days induced Parkinsonian-like symptoms in mice, consistent with another report. 26 Additionally, baicalein showed dosedependent trends in improving rotenone-induced motor impairments based on the rotarod and hang tests (Figure 2).…”
Section: Discussionmentioning
confidence: 96%
“…The mice were randomly assigned to 5 groups according to their body weight (control group, model group, and 3 baicalein-treated groups). As previously described, 25,26 the model group was treated with rotenone alone (1 mg/kg/day i.p. in sunflower oil), and the baicalein groups were treated with rotenone and different doses of baicalein (10 mg/kg, 30 mg/kg, and 100 mg/kg).…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Carbohydrates including structural polysaccharides like β-glucan, chitin, hemicellulose and pectin constitute the most abundant macronutrient of mushrooms, followed by protein and unsaturated fatty acids with a higher contribution of linoleic acid; an important precursor of long-chain n-6 fatty acids for humans [1,3]. Edible mushroom derived proteins lectins [2], amino acid ergothioneine [4], flavonoids [5] and polysaccharides categorized as glucans with β-type glycosidic bonds have been proposed as bioactive components responsible for regulation of the gut microbiome, modulation of the host immune response, hypolipidemic and anti-oxidant activity [6][7][8][9][10][11]. In addition, neuroprotective and antiageing properties of mushroom and isolated compounds like ergothioneine have been proposed for use against age related disorders [12][13][14][15][16][17][18], through the anti-inflammatory action purportedly regulated by changes in the composition of the intestinal microbiome.…”
Section: Introductionmentioning
confidence: 99%